Individual wave overtopping at coastal structures: A critical review and the existing challenges. (January 2021) - Koosheh, Ali; Etemad-Shahidi, Amir; Cartwright, Nick; Tomlinson, Rodger; van Gent, Marcel R.A.
Highlights: The basic concepts of the individual wave overtopping at coastal structures are reviewed. The temporal evolutions of the overtopping flow thickness/velocity along with the calculation of the overtopping discharge are discussed. The most common experimental measurement and data analysis techniques with an emphasis on their advantages and limitations are discussed. Abstract: Conventionally, allowable mean overtopping discharge is used as a design criterion for coastal structures. The mean overtopping discharge needs to be limited to ensure structural stability as well as the safety of people, vehicles, and properties behind the structure. Nowadays, limits for the maximum individual overtopping volumes are also specified in the design manuals, which requires the study of wave overtopping in wave-by-wave form. In some cases, in order to achieve more reliable safety for pedestrians and vehicles or to assess the stability of the inner slope, the maximum velocity and thickness of the overtopping flow need to be considered as well. The present paper aims to review the basic concepts of the individual wave overtopping such as the estimation of the probability of overtopping and the statistical methods to study the distribution of individual overtopping volumes. The temporal evolutions of the overtopping flow thickness / velocity along with the calculation of the overtopping discharge are discussed. Moreover, since the continuous recording of parameters is required for the study of individual wave overtopping, the most common experimental measurement and data analysis techniques with an emphasis on their advantages and limitations are discussed.